(untitled) (Canadian Journal of Native Studies, 2026)
The American anthropologist Vincent Crapanzano eulogizes the Navajo and Apache in his work Imaginary Horizons: An Essay in Literary-Philosophical Anthropology in order to linguistically capture the essence of Self and Other, in the spirit of mutual celebration. The difficult path to striking the delicate balance necessary to speak about the other when he is not always part of the conversation is delivered in this article by looking at figures of speech that are used to connect the interlocutors, but which have in-built distancing power that unfortunately involuntarily temporally relegates the native (excludes him because his physical absence signifies that he exists in a not-so-distant past in comparison to the interlocutor telling the story, in the present). This is evident in the poetic appropriation of the myth of the noble savage as well as the hinterland metaphor, which are used for describing native characters and their geographical origin. This piece discusses the difficulty to speak about aboriginal subjects by non-aboriginal researchers. It is shown that imagination is the work that reconnects, and poetry the work that gives voice.